HDL as a Biomarker of Rejection in Heart Transplant - Wilma Gonzalez; Pablo I. Altieri; Hector Banchs; Diego Iravedra; Rafael Calderon; Ivan Gonzalez-Cancel; Carmen Gurrea; Nelson Escobales; Maria Crespo (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2014)
Background: One hundred once patients underwent heart transplants due to multiple causes. These patients included 36 females and 65 males whose mean age was 51 years.  Objective: To study metabolic and lipid changes after heart transplantation with emphasis on HDL in rejected and non rejected hearts. Methods: The metabolic changes pre and post transplant were analyzed. Results:  1. Body mass index (BMI): 25 ± 4 - 28 ± 5 kg/ m2 (P<0.05) 2. Systolic blood pressure (sBP): 107 ± 17 - 131 ± 20mmHg (P<0.05) 3. Diastolic blood pressure (dBP): 70 ± 13 - 81 ± 10 mmHg(P<0.05) 4. Fasting blood sugar (FBS): 107 ± 37- 117 ± 55 mg%(0.164) (non significant) 5. Cholesterol: 170 ± 55 - 189 ± 32 mg/dl(P<0.05) 6. High density lipoprotein (HDL): 38 ± 16 - 52 ± 17 mg/dl (P<0.05) 7. Low density lipoprotein (LDL): 99 ± 20- 83 ± 15 mg/dl (0.34). 8. Triglycerides: 163 ± 10 -188 ± 12 mg/dl (0.144). Conclusions: The heart transplant patients developed metabolic syndrome (MetS). The elevated HDL levels observed after transplantation are indicative of role of immunologic reaction to chronic rejection processes. The patients who died of rejection (19) exhibited greater elevations in HDL that those who did not (47 ± 22 - 71 ± 40 mg/dl, P<0.05). Seven autopsies were performed and revealed severe atherosclerotic changes in the aorta and coronary arteries that were likely related to dysfunctional HDL. The transplanted hearts were 21 years old. The high levels and persistent elevation of HDL observed in the rejected group can be used as a biomarker of rejection and this will help to change the anti-rejection protocol to try to avoid the rejection of the implanted heart. LDL was found to be a factor in the progressive atherosclerotic process because the level was reduced post transplant.